TTF‐1 and napsin A on cell blocks and supernatants of pleural fluids for labeling malignant effusions. Issue 5 (14th April 2015) - Porcel, José M.; Palma, Rosa; Bielsa, Silvia; Esquerda, Aureli; Gatius, Sonia; Matias‐Guiu, Xavier; Salud, Antonieta
<x xml:space="preserve">Abstract</x> In this retrospective study of 80 pleural effusions, the combination of thyroid transcription factor 1 (TTF‐1) and napsin A immunostaining on fluid cell blocks was positive in 80% of lung adenocarcinomas. Although measuring TTF‐1 pleural fluid concentrations was of no value, quantification of napsin A levels allowed the identification of one third of the double‐negative stained lung adenocarcinomas, with an overall accuracy similar to classical tumour markers for malignant–benign discrimination (sensitivity 40%, specificity 100%).